M-ary Amplitude Shift Keying Power and Information Synchronous Transmission Based on Phase-Shifted Full-Bridge - Xin Zhang; Xuetong Pan; Yuehua Geng; Zhiqi Chu; Rongmei Han; Ming Xue (Applied Sciences, 2022)
This paper proposes an M-ary amplitude shift keying (MASK) power and information synchronous transmission system based on phase-shifted full-bridge (PSFB) for applications in wireless power transmission (WPT). The Pulse Width Modulation (PWM) waveform uses different phases to control the MOSFET in the full-bridge inverter for MASK modulation. The inverter voltage generates M amplitude transformation, forming a comprehensive power information flow. The demodulation circuit processes the information transmitted to the secondary side, following the power supply with a differential amplifier, to realize synchronous transmission of power supply and information. Compared with conventional amplitude modulation, the system’s volume is significantly reduced, and the DC-DC modulation circuit has no filtering effect. It transmits comprehensive high-level data and improves the information transmission rate from the perspective of bit width. In the experiment, 16-bit width data are transmitted, and the bit rate is increased by four times compared to conventional amplitude modulation. Combined with DSP, the designed demodulation circuit reduces the voltage amplitude fluctuation at the receiving end to 5% and minimizes the impact of amplitude modulation voltage fluctuation on the system.